Development of the Liverpool Jewry Historical Database - Philip Sapiro (Genealogy)
The Liverpool Jewish community was the earliest to be formed in the north of England (c1745) and for much of the 19th century, it was the largest UK Jewish community outside London. However, examination of this important minority community from a social, demographic, and genealogical perspective has been severely hampered by the lack of a unified source of information about Jewish individuals and families resident in the area during the 18th and 19th centuries. This paper describes how a searchable database of all Jewish persons with a documented connection with the Liverpool area, from the earliest times to 1881, has been produced as a resource for historical, demographic, sociological, and genealogical research. It explains how Jewish individuals were identified by a novel use of distinctive names, occupations, and birthplaces in the secular census and vital records and, in combination with extant records held within the Jewish community, have been used to produce a database of several thousand persons, linked into family groups. It concludes that the principal aim of the project has been achieved, and the approach could act as a template for other religion/ethnicity-based groups.